2019
DOI: 10.1111/jocn.15056
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental care for people with cognitive impairment in the hospital setting: A study combining positive organisational scholarship and video‐reflexive ethnography

Abstract: Aims and objectives:To clarify how high-quality fundamentals of care for people with dementia and/or delirium were practised in a specialist geriatric evaluation and management unit.Background: Older people with cognitive impairment represent a significant number of people who are admitted to hospital. They are at increased risk of dying, readmission and long hospital stays, relative to those without cognitive impairment. There is an urgent need to elucidate the conditions that underpin safe and high-quality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…The particular needs of older patients with cognitive impairment are often poorly recognized by hospital staff. Collier et al. (2020) found much can be done in the hospital setting to meet patients’ fundamental needs if the team is supported to translate person-centred care from rhetoric to reality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The particular needs of older patients with cognitive impairment are often poorly recognized by hospital staff. Collier et al. (2020) found much can be done in the hospital setting to meet patients’ fundamental needs if the team is supported to translate person-centred care from rhetoric to reality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A study of community health services revealed the importance of time with patients, as well as creative ways of investing time in relationships (Dadich et al, 2018). Person-centredness, teamwork and particular qualities of physical spaces were key to professionals' brilliant care for people with cognitive impairment (Collier et al, 2020). Collier et al (2019) connected brilliance in home-based palliative care with anticipatory action (proactively addressing individualized needs with families) and flexible adaptability (balancing building relationships with administrative requirements).…”
Section: Brilliance In Healthcarementioning
confidence: 99%
“…Since its advent, POS has been extended into healthcare (POSH) to intentionally consider, make sense of, and raise the profile of those instances within organisational life—be they large-scale or modest—that exceed the expectation of those who deliver, manage, administer, or receive healthcare, sensu lato [ 86 , 87 , 88 ]. This has also involved the use of the methodology, video reflexive ethnography (POSH-VRE)—detail on this methodology can be sourced elsewhere [ 89 , 90 , 91 , 92 , 93 ].…”
Section: Introductionmentioning
confidence: 99%